2016
DOI: 10.1055/s-0042-115171
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Surface Properties, and Therapeutic Applications of Gold Nanoparticles in Biomedicine

Abstract: Gold nanoparticles (AuNPs) due to their unique properties and manifold surface functionalities have been applied in bio-nanotechnology. The application of GNPs in recent medical and biological research is very extensive. Especially it involves applications such as detection and photothermalysis of microorganisms and cancer stem cells, biosensors; optical bio-imaging and observing of cells and these nanostructures also serve as practical platforms for therapeutic agents. In this review we studied all therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…In recent years, nanotechnology-based drug delivery systems (DDSs) have been widely developed and various nanomaterials such as graphene oxides [84], polymeric nanoparticles [85][86][87], MS [88][89][90][91] and AuNPs [92] have been investigated as drug delivery vehicles. AuNPs were the most investigated nanoparticles as DDSs, but due to their toxicity and biocompatibility issues they encountered various limits in clinical applications [93].…”
Section: Drug Deliverymentioning
confidence: 99%
“…In recent years, nanotechnology-based drug delivery systems (DDSs) have been widely developed and various nanomaterials such as graphene oxides [84], polymeric nanoparticles [85][86][87], MS [88][89][90][91] and AuNPs [92] have been investigated as drug delivery vehicles. AuNPs were the most investigated nanoparticles as DDSs, but due to their toxicity and biocompatibility issues they encountered various limits in clinical applications [93].…”
Section: Drug Deliverymentioning
confidence: 99%
“…Nanotechnology can play an important role in medicine, specifically in the early disease detection, improved diagnosis, and development of personalized treatments for chronic and infectious diseases [ 27 ]. Biocompatible AuNPs have been widely studied and applied in the diagnosis and treatment of cancer [ 28 ]. In addition, several studies indicated the intrinsic antitumor property of AuNPs that were able to selectively kill cancer cells [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of cancer increases after age 50 [2]. There are several strategies to inhibit and diagnosis the several steps of carcinogenesis [3][4][5][6][7]. The major approach considered is a protective strategy, which blocks the toxic matters, as well as the mutagenic effects, which accordingly prevents tumor initiation and promotion [8,9].…”
Section: Introductionmentioning
confidence: 99%